USING POSTERS IN EFL CLASSROOM: AN ELEMENTARY SCHOOL CASE - Sabriye Şener; Derya Bostan (Informascope, 2017)
It is assumed that vocabulary learning is an important component of learning a second or foreign language. There is also an agreement that it is central to language and of critical importance to the typical language learner. Since vocabulary knowledge is what foreign language learners most need, it is necessary to facilitate this process. The present study aims to determine the effect of posters on the vocabulary learning of students without any teacher instruction. It also aims to explore gender differences in learning vocabulary items on posters. The participants of the study include 54 fourth graders, studying at an elementary school in Muğla. The study was carried out during 2015-2016 academic year. The data were gathered by means of a vocabulary test containing 30 items that was used as the pre and post-test. Data analysis showed that posters in language classrooms helped vocabulary learning process. The mean score of the experimental group has increased from M=6.72 to M=14.24. Moreover, a significant difference was determined between the scores of females and males. The study showed that the post-test scores of females (M= 16.15) and males (M=12.69) were significantly different. It can be concluded that in foreign language classrooms utilizing from posters can be beneficial. Keywords: posters, teacher instruction, peripheral learning, vocabulary